Selecting salt-tolerant clones and evaluating genetic variability to obtain parents of new diploid and tetraploid germplasm in rhodesgrass (Chloris gayana K.) - Ribotta, Andrea Noemi; Griffa, Sabrina Mariana; Diaz, Daniel Gustavo; Carloni, Edgardo José; Lopez Colomba, Eliana; Tommasino, Exequiel Arturo; Quiroga, Mariana Paola; Luna, Celina Mercedes; Grunberg, Karina (2018)
We evaluated survival percentage under salt stress in 46 diploid and tetraploid clones of rhodesgrass (Chloris gayana K.) with the aim of obtaining salt tolerant clones. Fifteen clones were selected at 600 mM NaCl under hydroponic conditions. Survival percentage of the selected clones ranged between 50–100% and 50–75% for diploid and tetraploid clones, respectively. Genetic diversity among the 15 salt-tolerant clones was assessed using amplified fragment length polymorphism (AFLP). All tetraploid clones showed genetic diversity, whereas the diploid group included some genetically related clones. Clones tolerant at 600 mM NaCl and showed genetic diversity are proposed as parents for new synthetic varieties of each rhodesgrass ploidy.